Formulation and Stability Evaluation of Sunscreen Cream: Utilization of Methyl Cinnamate Isolate from Alpinia galanga L. Rhizome as a Photoprotective Agent - Yola Desnera Putri; Alidya Canticha Sari; Deby Tristiyanti; Adit Andriyannto (Jurnal Ilmiah Farmako Bahari, 2026)
Methyl cinnamate isolate is an aromatic ester compound with a conjugated chromophore system capable of absorbing UV-B radiation, making it a promising candidate for sunscreen formulations. This study aimed to determine the optimum concentration of methyl cinnamate isolate based on its sun protection factor (SPF) and to develop a sunscreen cream with satisfactory physical stability. Methyl cinnamate isolate solutions were prepared at concentrations of 1000, 2000, 3000, 4000, and 5000 ppm and screened for SPF activity. The concentration yielding the highest SPF value was incorporated into cream formulations containing different stearic acid concentrations as an emulsifier (F1: 8% w/w and F2: 10% w/w). The resulting formulations were assessed for SPF, physical characteristics during 28 days of storage at room temperature, microbiological quality, and methyl cinnamate content under accelerated stability conditions (40 ± 2°C and 75 ± 5% RH). The isolate at 5000 ppm (0.5%) exhibited the highest SPF value of 33.49, corresponding to the ultra-protection category. Both formulations maintained acceptable physical characteristics throughout the storage period. At day 28, SPF values were 13.87 for F1 and 17.02 for F2, with F2 remaining within the ultra-protection category. After three months of accelerated stability testing, methyl cinnamate content was 47.62% in F1 and 68.32% in F2. Microbiological evaluation also revealed contamination based on total plate count and yeast–mold count analyses. These findings indicate that methyl cinnamate isolate has potential as a sunscreen active ingredient; however, further formulation optimization and preservative incorporation are required to improve chemical stability and microbiological quality.